Collagen-based scaffolds for heart valve tissue engineering - Chen, Q (2013)
Tissue engineered heart valve (TEHV) is believed to be a promising candidate for curative heart valve replacements. Collagen, elastin and chondroitin-4-sulfate (C4S) comprise the extra-cellular matrix (ECM) of native heart valves and therefore are suitable materials for TEHV scaffolds. Freeze-drying technique was able to produce scaffolds with relative densities of 0.3%-2.0% and pore sizes of 33.2µm-201.5µm, without having any major effects on the ultra-structures on the scaffold materials. Subsequent dehydrothermal (DHT) treatment and ultra-violet (UV) irradiation introduced inter- or intra-molecular crosslinks in the scaffolds in forms of ester and amide bonds, as well as the accompanying denaturation of the proteins (i.e. ultra-structure transition from helices to random coils). The collagen-based scaffolds had tensile, compressive and effective bending moduli ranging from 39.8kPa to 1082kPa, from 2.4kPa to 213.9kPa, and from 11.0kPa to 415.8kPa, respectively. The different behaviours of the wall stretching and the wall buckling in the individual pores of the scaffolds contributed to the different tensile, compressive and bending moduli. The mechanical properties could be tailored through controlling the freezing temperature, the relative density and the composition of the scaffolds. A lower freezing temperature might lead to lower mechanical properties because different pore structures were introduced. When the the relative density of the scaffold increased, the values of the moduli increased exponentially, with an exponential dependence factor larger for the compressive modulus than for the tensile modulus. Adding elastin or C4S into the collagen scaffolds lowered the mechanical properties due to the decrease in the collagen content. Layered structures that combined collagen-rich layers with elastin-rich and/or C4S -rich layers allowed the scaffolds to make use of the different mechanical properties of different layers, and hence to show anisotropic bending behaviour depending on the loading directions. The lower effective bending modulus (9.6 to 25.0kPa) in the with curvature (WC) direction than that (18.1kPa to 39.3kPa) in the against curvature (AC) direction mimicked the characteristic behaviour of the native heart valves and would be beneficial for a mechanically desirable TEHV. The DHT treatment and UV irradiation were able to increase the mechanical properties of the scaffolds to up to 2.5 times of the original values, by reinforcing the scaffold materials with more crosslinks. In the hydrated status, the hydrophilic C4S improved the water uptake ability of the scaffold and the hydrophobic elastin reduced it. The hydrated layered scaffolds still exhibited bending anisotropy despite much lower effective bending modulus. Finite element models of the scaffolds produced results that were in agreement with the experiments, and enabled us to perform distributed loading and internal stress analysis on the scaffolds. The collagen-based scaffolds were seeded with cardiosphere-derived cells (CDCs), and they attached to the scaffolds and showed visible cell division, proliferation and migration. The CDCs exhibited preferred proliferation behaviours on the collagen-C4S scaffolds to that on the collagen-elastin scaffolds because of the cell affinity to the C4S, as well as the elastin-induced contractile cell phenotype and scaffold volume shrinkage. This difference seemed to be less evident in the layered scaffolds due to the cell communication between the layers. The crosslinking process also had effects on the cell proliferation in the ways that it induced ultra-structure changes or volume shrinkage in the scaffolds. The layered scaffold-cell constructs designed and produced in this study served as a forwarding step towards a mechanically desirable and biologically active TEHV.